Rethinking the human through Anna Maria Ortese: for an ecological critique of literature - Sara Gristina (Finzioni, 2024)
The presents reflections aim to highlight the importance and necessity of creating a discourse leading to an entirely new modus cogitandi for humans in environmental terms. Consequently, this discourse should lead to a repositioning and reevaluation of Western principles that have resulted in the removal of nature from the horizon and commitment of human political, social, and cultural thought. These premises underlie a critical study of texts from an ecological perspective and the philosophy of Anna Maria Ortese, proving to be painfully relevant to the current climate emergency and crisis that humanity is experiencing in this historical moment.